Crystallization of enzyme and method for producing same - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Leow, Thean Chor (2006)
New improved method for enzyme crystallization, which is simple and cheap, and which is compatible to industrial requirements.